OBM Transplantation 2020
DOI: 10.21926/obm.transplant.2002110
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Bacterial Infections before and after Liver Transplantation

Abstract: Bacterial infection represents a common event in the natural history of cirrhosis, especially in patients with end-stage liver disease. An episode of bacterial infection may significantly modify a patient's outcome in the setting of liver transplantation (LT) by impairing hepatic and extrahepatic organ functions, both in pre-operative and post-operative phases. Infections caused by multidrug-resistant organisms (MDRO) are increasing in cirrhosis due to high antibiotic exposure and hospitalizations. This issue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
0
1
1
Order By: Relevance
“…The incidence of MDRO infections has been increasing among LTR in the last decade [5,12,15,16,22,23]. We report a relatively lower prevalence of MDRO colonisation of 33% in our cohort of patients in contrast to 62%, 48%, and 45% reported by Phichaphop et al, Alcamo et al, and Beranger et al, respectively, in paediatric LTR [4,5,10].…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…The incidence of MDRO infections has been increasing among LTR in the last decade [5,12,15,16,22,23]. We report a relatively lower prevalence of MDRO colonisation of 33% in our cohort of patients in contrast to 62%, 48%, and 45% reported by Phichaphop et al, Alcamo et al, and Beranger et al, respectively, in paediatric LTR [4,5,10].…”
Section: Discussioncontrasting
confidence: 42%
“…MDRO has been reported to be associated with high mortality of 5-7% in paediatric LTR and 15-60% in adult LTR, in contrast to no mortality in our cohort [1,5,10,12,13]. Several adult and paediatric LTR studies have demonstrated that MDRO infections pretransplantation affects post-transplant survival [10,22]. GN-MDRO has been particularly associated with a higher morbidity and mortality in children and adult patients before and after transplant in comparison to GP-MDRO [3,11,15].…”
Section: Discussionmentioning
confidence: 51%